2013
DOI: 10.2175/193864713813536985
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Impacts of Thermal Activated Sludge Pretreatment and Development of a Pretreatment Model

Abstract: Waste activated sludge (WAS) pretreatment technologies are typically evaluated in terms of the associated improvement in biogas and sludge production during digestion and post-digestion dewaterability. However, WAS properties, and hence the impact of pretreatment on WAS properties, are dependent upon the raw wastewater composition and configuration of the wastewater treatment plant (WWTP). A generally accepted means of characterizing and comparing all pretreatment processes does not exist. The motivation for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Thus, the decrease in the VSS/TSS ratio found was only 7% across all three Systems and was statistically insignificant. Bougrier et al (2008) and Burger (2012) reported 9% and 10% decreases in the VSS/TSS ratio of a sludge that was pretreated at 150 0 C. Therefore, the ratio found from this study was comparable to the findings of literature mentioned above. Thus, it was concluded that no mineralization occurred during pretreatment and only solubilisation took place to convert a PCOD to sCOD.…”
Section: Suspended Solidssupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, the decrease in the VSS/TSS ratio found was only 7% across all three Systems and was statistically insignificant. Bougrier et al (2008) and Burger (2012) reported 9% and 10% decreases in the VSS/TSS ratio of a sludge that was pretreated at 150 0 C. Therefore, the ratio found from this study was comparable to the findings of literature mentioned above. Thus, it was concluded that no mineralization occurred during pretreatment and only solubilisation took place to convert a PCOD to sCOD.…”
Section: Suspended Solidssupporting
confidence: 90%
“…Thermal hydrolysis processes can be categorized in two groups; pretreatment below 100 0 C is considered a low temperature (LT) pretreatment and pretreatment above 100 0 C under pressure is known as high pressure thermal hydrolysis (HPTH) (Burger, 2012). LT pre-treatment's have been found to increase sludge solubilisation with less energy than HPTH, but do not improve sludge digestion (Nielsen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…To normalize the results to feed concentrations the extent of COD solubilisation was calculated using Eq. 2 [16].…”
Section: Resultsmentioning
confidence: 99%